Structural, dynamical, and thermodynamical properties of carbon nanotube polycarbonate composites: a molecular dynamics study - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2012)
All-atom molecular dynamics simulations are performed on pure monomer and trimer of polycarbonate and their mixtures with different molecular weight percentages of embedded single walled carbon nanotubes at different temperatures to study the structural and dynamical properties of the composite system. The diffusion behaviors of monomer, trimer of polycarbonate and carbon nanotubes in composite matrices are investigated and compared with pure matrices in details. Both structural and dynamical properties indicate the weak interaction between the nanotubes and matrix molecules. The high tendency of nanotubes to form bundles is observed during simulation. The bundle formation free energy has been calculated from the potential of mean force calculations. The mechanism and energetics of bundle formation is explored in the atomistic scale. The formation of the carbon nanotube bundle is a favorable process in the oligomeric polycarbonate matrix.

Structure of nanorod assembly in the gyroid phase of diblock copolymer - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Diblock copolymers undergo microphase separation to form various microstructures, for example, lamellar, gyroid, cylindrical, cubic phases depending on compostion and segregation strength (Flory-Huggins parameter chi). Thus, it can act as template to organize doped nanomaterials into different 3D self-assembled structures located within the block copolymer matrix. Gyroid phase is One of the microstructures formed by block copolymer. It has a curved interfacial surface providing confinements throughout the matrix and thus can regulate the shape and sizes of self-assembled nanorods doped in it. Mesoscale simulation of model systems has been performed to explore the structure and dynamics of self-assembly of bundles formed by nanorods of different flexibilities in the gyroid phase of diblock copolymer matrix. Bundles of different shapes and sizes have been found to be formed depending on the nanorod bending flexibility and copolymer-nanorod interactions. The shape anisotropy (kappa(2)) and radius of gyration (R-g(2)) of bundles situated at different interfacial confining locations of block copolymer-matrices have been investigated as a function of nanorod flexibility and nanorod-diblock copolymer miscibility.